Response Surface Methodology Optimization of Deproteinization from Sardine (Sardina Pilchardus) Scale of Moroccan Coast - Bellali, F; Kharroubi, M; Lahlou, FZ; Lotfi, M; Radi, Y; Bourhim, N (The International Journal of Biotechnology, 2013)
The present study was designed to determine the optimum conditions for the deproteinization of Moroccan sardine scale (Sardina pilchardus) by using a central composite design of response surface methodology.A central composite design was consisted of eight experimental points and five replications at the center point, which was used to determine the effects of two independent variables (NaOH concentration and treatment time) on hydroxyproline content. A second-order polynomial model was used for predicting the response. Until now, a very few researchers has focused on deproteinization of scale by using a surface response methodology. The results showed the optimal conditions for lowest value of response when the concentration of NaOH was 0.5% and the treatment time was 4h. The experimental value for the hydroxyproline content was 2.46mg/l. That result was in agreement with the predicted value, which indicates that the model used was adequate for deproteinization step.